2020
DOI: 10.3390/plants9111598
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Upland Cotton (Gossypium hirsutum L.) Lines to Irrigated and Rainfed Conditions of Texas High Plains

Abstract: Understanding drought stress responses and the identification of phenotypic traits associated with drought are key factors in breeding for sustainable cotton production in limited irrigation water of semi-arid environments. The objective of this study was to evaluate the responses of upland cotton lines to rainfed and irrigated conditions. We compared selected agronomic traits over time, final yield and fiber quality of cotton lines grown in irrigated and rainfed trials. Under rainfed conditions, the average n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…According to the heatmap, the genotypes G4, G9, and G10 in both irrigation conditions, G2 and G3 in normal irrigation and water-deficit stress conditions, respectively, had the highest cotton yield across most years studied, while the genotypes G8 and G6 had the lowest cotton yield under normal irrigation and water-deficit stress conditions, respectively. Ayele et al [30], Yehia [34], and Eid et al [16] observed the same trend when compared to water-deficit stress conditions; cotton genotypes in normal irrigation conditions showed higher seed cotton yield, which ranged from 11.12% by G3 to 28.03% by G7, suggesting genetic variability in eleven studied genotypes for drought tolerance. Also, Grzesiak et al [13] and Sun et al [15] found a considerable decrease in yield in drought-sensitive genotypes, whereas yield decline was significantly lower in droughttolerant genotypes.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…According to the heatmap, the genotypes G4, G9, and G10 in both irrigation conditions, G2 and G3 in normal irrigation and water-deficit stress conditions, respectively, had the highest cotton yield across most years studied, while the genotypes G8 and G6 had the lowest cotton yield under normal irrigation and water-deficit stress conditions, respectively. Ayele et al [30], Yehia [34], and Eid et al [16] observed the same trend when compared to water-deficit stress conditions; cotton genotypes in normal irrigation conditions showed higher seed cotton yield, which ranged from 11.12% by G3 to 28.03% by G7, suggesting genetic variability in eleven studied genotypes for drought tolerance. Also, Grzesiak et al [13] and Sun et al [15] found a considerable decrease in yield in drought-sensitive genotypes, whereas yield decline was significantly lower in droughttolerant genotypes.…”
Section: Discussionmentioning
confidence: 64%
“…These findings show that genotypes have a lot of variation and are distinct, allowing us to choose genotypes under water-deficit stress conditions. In both irrigated and rainfed trials, Ayele et al [30] and Abo Sen et al [31] found high variability in yield among cotton genotypes. Our findings also revealed the variability and inconsistency in seed cotton yield responses among investigated genotypes in both irrigation conditions over a five-year period.…”
Section: Discussionmentioning
confidence: 98%
“…Ayele et al (2020),Yehia (2020), andEid et al (2022) observed the same trend when compared to water-de cit stress conditions; cotton genotypes in normal irrigation conditions showed higher seed cotton yield, which ranged from 11.12% by G3 to 28.03% by G7, suggesting genetic variability in eleven studied genotypes for drought tolerance. Also,Grzesiak et al (2019) andSun et al (…”
mentioning
confidence: 55%
“…Ayele et al (2020) and AboSen et al (2022) found high variability in yield among cotton genotypes. Our ndings also revealed the variability and inconsistency in seed cotton yield responses among investigated genotypes in both irrigation conditions over a ve-year period.…”
mentioning
confidence: 95%
“… Chaves and Pereira (2003) and Onaga and Wydra (2016) investigated the influence of water stress on cotton seed germination, suggesting that cotton seeds under different drought stress were associated with decreases in water potential, germination rate, index, seedling height, root length, root-to stem ratio, dry weight and in associated with the fresh weight of young seedlings all decreased to varying degrees ( Pettigrew, 2001 ; Fahad et al, 2017 ). Studying the growth and development of cotton in Jiangsu Province under drought conditions ( Zhao et al, 2020 ), it was found that cotton growth was initially inhibited under drought conditions, and the plant height and leaf emergence rates were significantly slowed ( Gao et al, 2020 ) found that when cotton was subjected to drought stress at different growth stages, its growth, development and yield were affected to some extent, and the influence from largest to smallest was the flower-boll, bud, maturity and seedling stage ( Ullah et al, 2017 ; Ayele et al, 2020 ). The results show that drought resistant germplasm materials can effectively reduce water loss by increasing atmospheric pore resistance and reducing evapotranspiration intensity, thereby ensuring photochemical efficiency.…”
Section: Effects Of Non-living Stress On Cotton Growth and Developmentmentioning
confidence: 99%